Prevalence of Helicobacter pylori among Patients with Gastrointestinal Tract (GIT) Symptoms: A Retrospective Study at Selected Africa Air Rescue (AAR) Clinics in Kampala, Uganda, from 2015 to 2019. (8th November 2021) - Namyalo, Edity; Nyakarahuka, Luke; Afayoa, Matthias; Baziira, Joel; Tamale, Andrew; Atuhaire, G. Collins; Kungu, Joseph M.
Abstract : Background . Helicobacter pylori (HP) infection is extremely common worldwide, with almost half of the world's population infected. In Uganda, no study has been done on the trends of the prevalence of H . pylori infection in the affluent population. Therefore, this retrospective cross-sectional study aimed at determining the trend of H . pylori prevalence among affluent patients presenting with gastrointestinal (GIT) symptoms whose stool samples were tested at selected AAR clinics in Kampala area. Patients were tested for Helicobacter pylori infection using the stool antigen test between January 2015 and December 2019. Results . The overall 5-year H. pylori prevalence was 35.7% (1298/3634). The prevalence was higher in males (36.0% (736/2044)) than in females (35.4% (562/1590)), although not statistically significant (OR = 0.97, p = 0.680, 95% CI: 0.84–1.11). The prevalence of H . pylori infection was significantly higher (39.4%) among patients who belonged to the age group of 19–35 years (OR = 1.49, p < 0.001, 95% CI: 1.22–1.82). The prevalence for H . pylori among the age group of 19–35, the most productive age, could be attributed to work-related factors such as stress. The highest prevalence (43.4%) was recorded in 2018 and the lowest (21.4%) in 2015; however, the trend of H . pylori infection in the 5 years was fluctuating. Conclusion . H . pylori infestation is a preserve of not only the poor but also the elites. Stressful factors, especially in the age group of 19–35 years, should be appropriately managed.